GENETAL HYGIENE BEHAVIOR ASSOCIATED WITH THE EVENT OF LEUKORRHEA AT SMAN 1 GALUR, KULON PROGO DISTRICT - Afi Lutfiyati (JPKM: Jurnal Profesi Kesehatan Masyarakat, 2020)
Genital hygiene behavior were very important activity to prevent infection of reproductive organs and stayed healthy especially for women. The attitude of indifference in maintaining genital hygiene could lead to leukorrhea. Women of all ages could experience leukorrhea. Adolescents were part of a population at risk of experiencing leukorrhea, because adolescence were a period of transition and also the period of maturity of the sexual organs. The study aimed to identify the association between the behaviors of maintaining genital hygiene with the occurrence of leukorrhea at SMAN 1 Galur. This research type were quantitative with cross sectional approach. Samples were taken by stratified random sampling technique with respondents as many as 56 female students. The research instrument were using questionnaire. The results showed that some students maintain the genital hygiene behavior with fair category that is as many as 33 female students (58.9%). The occurrence of leukorrhea indicates that most female students of SMAN 1 Galur experienced physiological discharge as many as 48 (85,7%). The calculation result of statistic test were using Kendall tau-c test obtains p-value of 0.5950.05. There were no association between the behaviors to maintain genital hygiene with the occurrence of leukorrhea at SMAN 1 Galur.